Performance of Photovoltaic as Pump Drive for Alternator Characteristic Monitoring System - Herlambang, Yusuf Dewantoro (Eksergi, 2023)
The objectives of this research to generate electrical energy by making photovoltaic which utilizes the potential of solar radiation sources to drive the pump. There are 2 monocrystalline solar panels installed with a capacity of 100 Wp. Installation of solar panels at an angle of 7 ° based on geographic location in the Tambakboyo, Ambarawa, -7.263239"(Latitude) South Latitude and 110 °42'06.82 (Longitude) East Longitude. The test is carried out by turning on the pump for 1 hour within a period of time until 7 days. The parameters measured in the test are solar radiation data (W/m ²), voltage (V) and current (A) input from solar panels, battery input voltage, voltage and current input from the inverter, as well as the output voltage and current from the inverter. The results of test obtained the highest efficiency value of 12.854% at a voltage of 12.58 V and a current of 10.4 A.